2001
DOI: 10.2460/ajvr.2001.62.97
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of the endothelin receptor B mutation that causes lethal white foal syndrome in white-patterned horses

Abstract: In homozygotes, the Ile118Lys EDNRB mutation causes OLWS. In heterozygotes, the mutation is usually responsible for a frame overo phenotype. The frame pattern can be combined with other white patterns, making accurate estimation of EDNRB genotype by visual inspection difficult. Wide range of incidence of heterozygotes in various subtypes of white-patterned horses indicates different genetic control of these color patterns. Determination of EDNRB genotype by use of a DNA-based test is the only way to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…[11][12][13][14] Overo horses were further subclassified according to the 3 major genetically distinct overo patterns recognized by the APHA, including frame, splashed white overo, and sabino. 11,15 For 25 years, the person who classified the horses (KGM) has been involved in the evalu-ation of coat color pattern in American Paint Horses. 11,15 For 25 years, the person who classified the horses (KGM) has been involved in the evalu-ation of coat color pattern in American Paint Horses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Overo horses were further subclassified according to the 3 major genetically distinct overo patterns recognized by the APHA, including frame, splashed white overo, and sabino. 11,15 For 25 years, the person who classified the horses (KGM) has been involved in the evalu-ation of coat color pattern in American Paint Horses. 11,15 For 25 years, the person who classified the horses (KGM) has been involved in the evalu-ation of coat color pattern in American Paint Horses.…”
Section: Methodsmentioning
confidence: 99%
“…13,15 The genetic mutation causing the most common form of sabino overo, including the form in APHA horses, has been described and named sabino-1. In the heterozygous state, the gene yields the frame overo phenotype.…”
Section: Methodsmentioning
confidence: 99%
“…Prevalence of the deleterious allele is greatest in overo-type color patterns including frame overo, highly white calico overo and frame blend overo; in one study 94% of animals in these categories were heterozygous for the mutation (Santschi et al 2001). However, carriers have been identified that completely lack white spotting (Santschi et al 2001).…”
Section: Simple Genetic Diseases Of the Domestic Horsementioning
confidence: 97%
“…However, carriers have been identified that completely lack white spotting (Santschi et al 2001). Deafness has been significantly but not absolutely associated with the heterozygous state (Magdesian et al 2009).…”
Section: Simple Genetic Diseases Of the Domestic Horsementioning
confidence: 99%
“…It is believed that white markings and de-pigmentation patterns were favored as a means of both identifying owned individuals and distinguishing them from their wild relatives. Despite the practical usefulness of markings and their aesthetic desirability, pelage de-pigmentation is frequently associated with undesirable side effects, including neurological defects and eye disorders [7], [16][19].…”
Section: Introductionmentioning
confidence: 99%